Does basic need satisfaction mediate the link between stress exposure and well-being? A diary study among beginning teachers. (August 2017) - Aldrup, Karen; Klusmann, Uta; Lüdtke, Oliver
Abstract: An imbalance between work-related stressors and resources, which we refer to as stress exposure, is often found to impair teachers' occupational well-being. However, the psychological mechanisms that explain this relationship are mostly unknown. We assumed that satisfaction of the basic psychological needs for competence, relatedness with students, and relatedness with colleagues acts as a mediator. To test this assumption, we conducted a two-week diary study with 152 beginning teachers. A multilevel within-subject mediation analysis showed that teachers felt less work enthusiasm and more emotional exhaustion on days when stress exposure was high. Whereas the needs for competence and relatedness with students explained the association with work enthusiasm, the need for competence mediated the relationship with emotional exhaustion. Additionally, the least experienced teachers felt more emotional exhaustion when the need for relatedness with students was not satisfied. These findings add to our understanding of the daily intra-individual processes affecting beginning teachers' occupational well-being. Highlights: We study psychological mechanisms linking teachers' stress exposure and well-being. Use of a two-week diary study to discover dynamic intra-individual processes. Daily stress exposure predicts emotional exhaustion and work enthusiasm. The needs for competence and relatedness with students mediate this relationship. Relatedness with students is particularly important at the beginning of the career.